An Eggplant Recombinant Inbred Population Allows the Discovery of Metabolic QTLs Controlling Fruit Nutritional Quality - Sulli, Maria; Barchi, Lorenzo; Toppino, Laura; Diretto, Gianfranco; Sala, Tea; Lanteri, Sergio; Rotino, Giuseppe Leonardo; Giuliano, Giovanni (Frontiers in Plant Science, 2021)
Eggplant (Solanum melongena L.) represents the third most important crop of the Solanaceae family and is an important component of our daily diet. A population of 164 F6 Recombinant Inbred Lines (RILs), derived from two eggplant lines differing with respect to several key agronomic traits, ‘305E40’ and ‘67/3’, was grown to the commercial maturation stage and fruits were harvested, separated into peel and flesh, and subjected to LC-MS analysis. Through a combination of untargeted and targeted metabolomics approaches a number of metabolites belonging to the glycoalkaloid, anthocyanin and polyamine classes and showing a differential accumulation in the two parental lines and F1 hybrid were identified. Through metabolic profiling of the RILs, we identified several metabolomic quantitative trait loci (mQTLs) associated to the accumulation of those metabolites. Each of the metabolic traits proved to be controlled by one or more QTLs; for most of the traits, one major mQTL (PVE≥10%) was identified. Data on mQTL mapping and dominance-recessivity relationships of measured compounds in the parental lines and F1 hybrid, as well as an analysis of the candidate genes underlying the QTLs and of their sequence differences in the two parental lines suggested a series of candidate genes underlying the traits under study.